Bacteriophages isolated from Lake Michigan demonstrate broad host-range across several bacterial phyla. Issue 1 (December 2015) - Malki, Kema; Kula, Alex; Bruder, Katherine; Sible, Emily; Hatzopoulos, Thomas; Steidel, Stephanie; Watkins, Siobhan; Putonti, Catherine
Abstract Background The study of bacteriophages continues to generate key information about microbial interactions in the environment. Many phenotypic characteristics of bacteriophages cannot be examined by sequencing alone, further highlighting the necessity for isolation and examination of phages from environmental samples. While much of our current knowledge base has been generated by the study of marine phages, freshwater viruses are understudied in comparison. Our group has previously conducted metagenomics-based studies samples collected from Lake Michigan - the data presented in this study relate to four phages that were extracted from the same samples. Findings Four phages were extracted from Lake Michigan on the same bacterial host, exhibiting similar morphological characteristics as shown under transmission electron microscopy. Growth characteristics of the phages were unique to each isolate. Each phage demonstrated a host-range spanning several phyla of bacteria – to date, such a broad host-range is yet to be reported. Genomic data reveals genomes of a similar size, and close similarities between the Lake Michigan phages and the Pseudomonas phage PB1, however, the majority of annotated genes present were ORFans and little insight was offered into mechanisms for host-range. Conclusions The phages isolated from Lake Michigan are capable of infecting several bacterial phyla, and demonstrate varied phenotypic characteristics despite similarities in host preference, and at the genomic level. We propose that such a broad host-range is likely related to the oligotrophic nature of Lake Michigan, and the competitive benefit that this characteristic may lend to phages in nature.